RUSSIA’S INFORMATION SECURITY IN THE NORTHERN CAUCASUS: PROBLEMS AND HOW TO SETTLE THEM - -Emi SHAMSUEV, Magomed (CENTRAL ASIA AND THE CAUCASUS, 2012)
The Northern Caucasus, home to numerous ethnicities, is a challenge to the political administration and national security of the Russian Federation; many problems of state order and ethnic relationships, caused by rivalry among political and ethnic elites for power and influence, have reached a critical level. There are ethnic and clan contradictions and territorial disagreements.1 Today, the information security of the Northern Caucasus should be discussed at two levels—domestic and global. The former is related to the region’s status and role in Russia’s domestic policy and development and the latter to its place in Russia’s foreign policy and the interest of foreign states and international organizations in the macro region. In one of his books, Andrey Zdravomyslov wrote that the Northern Caucasus owed its international weight to the fact that it was situated at the crossing of geopolitical “power” lines, “the crossroads of geopolitical aims.”2 On 12 November 2009, in his address to the Federal Assembly, President of Russia Dmitry Medvedev pointed out that “our most serious, domestic political problem [is] the situation in the North Caucasus.”3 Information security in the Northern Caucasus is directly related to real and potential threats and challenges. In the last few years, their level and scope have increased many times over to become extremely dangerous.